Effects of spray drying on Lactobacillus plantarum BM-1 viability, resistance to simulated gastrointestinal digestion, and storage stability. Issue 2 (25th January 2016) - Zhu, Zhang; Luan, Chunguang; Zhang, Hongxing; Zhang, Liebing; Hao, Yanling
ABSTRACT: The aim of this study was to evaluate the applicability of spray drying in the production of high-viability powder of L. plantarum BM-1. Firstly, in order to improve the survival of L. plantarum BM-1 during spray drying, different protectants were added before drying. The results showed that the highest survival rate of 75.70% and the lowest moisture content of 3.67% were achieved with the combination of reconstituted skim milk (RSM) and equal weight sucrose as protective agent. The cell counts reduction of free L. plantarum BM-1 was 2.58 log CFU/ml after exposure to 60°C for 1 min, whereas the reduction in spray-dried cells protected by RSM and sucrose was only 0.08 log CFU/ml. After 120-min incubation in simulated gastric condition, cell counts of free L. plantarum BM-1 decreased approximately 1.4 log CFU/ml, whereas no significant ( p  > 0.05) reduction in spray-dried cells was observed. Compared to the free cells, the spray-dried cells also showed higher survival under bile salts stress. In addition, the bacteriocin production of L. plantarum BM-1 was not affected during spray drying. Furthermore, the survival rate of spray-dried powder reached 98% after storage for 2 months at 4°C, and a nitrogen replacement package was shown to be better than a vacuum package and air-sealed package at room temperature. Therefore, the combination of equal weight RSM and sucrose is a promising protective agent for L. plantarum BM-1 during spray drying.